Chronic Q Fever with Vascular Involvement: Progressive Abdominal Pain in a Patient with Aortic Aneurysm Repair in the United States - Zanthia Wiley; Sujan Reddy; Kara M. Jacobs Slifka; David C. Brandon; John Jernigan; Gilbert J. Kersh; Paige A. Armstrong (Case Reports in Infectious Diseases)
Q fever is a zoonotic bacterial infection caused by Coxiella burnetii. Chronic Q fever comprises less than five percent of all Q fever cases and, of those, endocarditis is the most common presentation (up to 78% of cases), followed by vascular involvement. Risk factors for chronic Q fever with vascular involvement include previous vascular surgery, preexisting valvular defects, aneurysms, and vascular prostheses. The most common symptoms of chronic Q fever with vascular involvement are nonspecific, including weight loss, fatigue, and abdominal pain. Criteria for diagnosis of chronic Q fever include clinical evidence of infection and laboratory criteria (antibody detection, detection of Coxiella burnetii DNA, or growth in culture). Treatment of chronic Q fever with vascular involvement includes a prolonged course of doxycycline and hydroxychloroquine (≥18 months) as well as early surgical intervention, which has been shown to improve survival. Mortality is high in untreated chronic Q fever. We report a case of chronic Q fever with vascular involvement in a 77-year-old man with prior infrarenal aortic aneurysm repair, who lived near a livestock farm in the southeastern United States.